Evaluation of oral health in patients with mental disorders attended at the clinic of oral diagnosis of a public university - Marina Sena Lopes Da Silva Sacchetto; Natália Silva Andrade; Maria Hellen Sâmia Fortes Brito; Divana Maria Martins Parente Lira; Simone Souza Lobão Veras Barros
INTRODUCTION: Many people suffering from mental disorders fail to adequately perform self-care, especially in relation to personal hygiene and in particular to oral hygiene. For these individuals, the prevention and ongoing clinical monitoring are essential. OBJECTIVE: To investigate the oral diseases that most affect patients with mental disorders attended in the Dental College of the Federal University of Piauí (UFPI). METHODOLOGY: Patients treated during the 2nd half of 2011 and 1st half of 2012 were examined. The DMFT index was used for evaluation of dental caries and the CPI index for periodontal evaluation. The statistical analyzes were performed with SPSS (Statistical Package for the Social Sciences), version 18.0, using a descriptive statistics to determine averages, standard deviations and frequencies. RESULT: 67.50% of the 40 patients had contact with the surgeon dentist for over one year, 95% performed their own oral hygiene and 70% did not use dental floss. The average of DMFT was 14.18. Of the patients, 49.13% needed of restorations of one surface and 60% needed dental prosthesis. Moreover, 33.75% of sextants evaluated had periodontal pockets. CONCLUSION: It can be noticed that patients with mental illness have a high risk of developing oral disorders, however, few carriers visite a dental professional regularly. In addition, the delay to seek treatment and lack of staff training, lead to solutions often crippling.